Understanding cultural barriers to the care of low-birth-weight infants in Papua, Indonesia: A qualitative descriptive study - Situmorang, Hotnida Erlin; Rustina, Yeni; Novieastari, Enie (Belitung Nursing Journal, 2025)
Background: Low birth weight (LBW) is a persistent public health challenge globally, including in Indonesia, particularly in remote areas like Papua. While biological risks are well documented, the influence of sociocultural factors on LBW infant care remains underexplored. There is a critical gap in understanding how cultural beliefs and family dynamics act as barriers to effective caregiving in these settings. Objective: This study aimed to explore cultural barriers to the care of LBW infants in Papua, Indonesia. Methods: A qualitative descriptive design was employed. Data were collected through face-to-face, semi-structured interviews with ten mothers of LBW infants in Jayapura, Papua, from May to July 2024. Interviews were transcribed verbatim and analyzed using inductive thematic analysis. Results: Inductive thematic analysis resulted in six themes: (1) Traditions and traditional practices during pregnancy and childrearing; (2) Perceptions of herbal remedies and traditional practices in managing infant health and growth; (3) Traditional care practices for LBW infants and their adaptation within community health efforts; (4) Challenges and obstacles for parents in caring for LBW infants; (5) Family support, roles, and hospital-based education in LBW care; and (6) Parental understanding, needs, and expectations regarding LBW care. Conclusion: Despite improvements in health information and services, ongoing cultural negotiation is needed to achieve optimal family-based LBW care. Nurses and other health workers should enhance cultural competence and employ patient-centered, culturally sensitive nursing care that integrates local traditions with evidence-based practice, aiming to improve infant health and reduce complications.